Modelling Vulnerability of Transportation Network Using Influence Diagrams - Titko, Michal; Zagorecki, Adam (Communications - Scientific letters of the University of Zilina, 2013)
The transportation network (TN) is important to serve the national priorities such as economic sustainability and growth, but it as well plays important role in disaster management and is subject to hazards. The understanding of the TN resilience and vulnerabilities is important for the national security. In this work we focus on the notion of TN vulnerability. We propose the use of a decision-theoretic approach based on Influence Diagrams (IDs). We argue that the use of IDs (1) provides an improved framework for risk assessment through more elaborate combining probabilities and consequences, and (2) facilitates knowledge elicitation from human experts through a structured approach to the problem. The proposed methodology is intended to be applied to the critical infrastructure.